Acinar cell carcinoma of the pancreas presenting as diffuse pancreatic enlargement: Two case reports and literature review. Issue 38 (September 2017) - Luo, Yaping; Hu, Guilan; Ma, Yanru; Guo, Ning; Li, Fang
Abstract: Rationale: Pancreatic acinar cell carcinoma (ACC) is a rare malignant tumor of exocrine pancreas. It is typically a well-marginated large solid mass arising in a certain aspect of the pancreas. Diffuse involvement of ACC in the pancreas is very rare, and may simulate pancreatitis in radiological findings. We report 2 cases of ACC presenting as diffuse enlargement of the pancreas due to tumor involvement without formation of a distinct mass. Patient concerns: The patients consisted of a 41-year-old man with weight loss and a 77-year-old man who was asymptomatic. Diagnoses: Computed tomography (CT) and 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT showed diffuse enlargement of the pancreas forming a sausage-like shape with homogenously increased FDG activity. Interventions: Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) biopsy of the pancreatic lesion was performed. Outcomes: Histopathology results from the pancreas confirmed the diagnosis of pancreatic ACC. Lessons: Because diffuse enlargement of the pancreas is a common imaging feature of pancreatitis, recognition of this rare morphologic pattern of ACC is important for radiological diagnosis of this tumor.